(untitled) (Journal of Engineering, 2006)
The optimum trajectory of a single or multi-stage satellite launcher guided with proportional navigation guidance (PNG) is addressed. The PNG is extended to compensate for the gravity effect. For the trajectory optimization problem, the launcher is modeled as a mass point flying around the center of the Earth. To provide a completely valid analysis, all known influences on the launcher trajectory have been considered; Empirical equations have been used in order to model the Earth standard atmosphere in SI units. A computer program had been constructed in order to simulate the trajectory of such launcher from the available initial conditions. Pegasus launcher is used as a hypothetical example. The simulator results show that the proportional navigation plus gravity compensation guidance gives fairly accurate results.